Clinical Characteristics of Alternaria Keratitis. (20th March 2014) - Hsiao, Ching-Hsi; Yeh, Lung-Kun; Chen, Hung-Chi; Lin, Hsin-Chiung; Chen, Phil Y. F.; Ma, David H. K.; Tan, Hsin-Yuan
Abstract : Purpose . Alternaria spp. are an uncommon cause of mycotic keratitis. Previous studies on Alternaria keratitis have generally been limited to case reports. We examined the clinical characteristics of Alternaria keratitis in this study. Methods. The characteristics and outcomes of 7 patients with culture-proven Alternaria keratitis treated in our hospital were compared with 25 previously reported cases. Results. The risk factors for Alternaria keratitis were trauma in 5 patients and soft contact lenses in 1 patient. Six patients with early diagnosis (<2 weeks) were cured with medical antimicrobial treatment; a patch graft was required in 1 patient with perforation. When incorporated with previous reports on Alternaria keratitis ( n = 32 ), 14 (44%) infections followed trauma, 10 (31%) were associated with preexisting corneal disease or previous ocular surgery, and 5 (16%) occurred in soft contact lens wearers. Successful medical treatment was achieved in 23 (72%) patients, including 10 out of 21 eyes (48%) treated with natamycin and/or amphotericin B. Therapeutic penetrating keratoplasty was performed in 9 (28%) cases. Conclusions . Alternaria keratitis is generally associated with specific risk factors and responds to medical treatment when early diagnosis is performed and prompt antifungal treatment is initiated.